The Incidence of Mucositis in Children with Chemotherapy Treatment - Sri Hendrawati; Ikeu Nurhidayah; Henny Suzana Mediani; Ai Mardhiyah (Journal of Nursing Care, 2019)
Currently, cancer is the top ten cause of child mortality in Indonesia. Chemotherapy is an effective intervention to treat cancer children, however, has side effects, including mucositis. The prevalence of mucositis in cancer children is estimated to reach 45−80%, which has implications for the children’s’ quality of life. The purpose of this study was to identify the occurrence of mucositis in cancer children who received chemotherapy treatment. The study was conducted at Dr. RSUP Hasan Sadikin Bandung. This research method was descriptive quantitative. The consecutive sampling technique was used to determine the respondent as the study sample so that 60 respondents were obtained. The process of collecting data used the Oral Assessment Guide (OAG) study instrument in the form of a checklist sheet. Data were analyzed using frequency distribution and percentage. The results showed that almost all cancer children with chemotherapy treatment experienced mucositis which is 53 people (88.3%) and a small proportion of 7 people (11.7%) did not experience mucositis. Almost all cancer children who get chemotherapy treatment experience mucositis. Nurses as health workers who are most often with patients should be able to improve nursing care for cancer children who receive chemotherapy treatment in minimizing the occurrence of mucositis by conducting routine mucositis assessment and oral care to improve the quality of life in cancer children